Laju Tumbuh Tanaman dan Produksi Kentang (Solanum tuberosum L.) Varietas Granola pada Pemberian Pupuk Organik Kascing dan Inokulasi Mikoriza Arbuskular - Nurhalisyah Nurhalisyah (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
The Crop Growth Rate and Yield of Potato (Solanum tuberosum L.) of Granola Variety Under Applying Earthworms Castings and Inoculants of Arbuscular MycorrhizaeABSTRACT. This study intends to identify the crop growth rate and yield of potato at the application earthworms castings and inoculants arbuscular mycorrhizae (AM). Using randomized block design with dual factorial. First factor was the application the earthworm castings with four levels of treatment, that are 0, 100, 200, and 300 gram casting per plants-1, respectively. Second was inoculants arbuscular mycorrhizae with four levels too, they are 0, 2.5, 5, and 7.5 gram per plant-1. Application of earthworm castings was conducted three days before planting, while mycorrhizae was performed at the time of cultivation. Crop growth rate increased with augmented age from 38-68 days after planting (dap) and then declined at 78-88 dap. The highest rate (0,0055 gr cm-2 day-1) occurred at the treatment by 300 g plant-1 and inoculants with AM 7.5 g plant-1 at age of 67 dap. The application of the organic fertilizer (earthworm castings) 300 g per plant-1 and AM inoculants 5 g plant-1give the highest productivity.